Cultural Branding as a Key in Positioning Schools: A Conceptual Model - Hidayatun, Hidayatun (IAIN Surakarta, 2017)
The increase of peopleâ€™s prosperity and education creates a change in their view about education and the need towards it. Consequently, their choice of educational institutions becomes more selective. On the other hand, the competition in this field becomes more viable due to the growth of the educational institutions. The management strategy should be evaluated. This paper discusses the interfaces between culture and school, especially those that refer to the branding. The study was carried out on a premise that creating a bond between the school and community is possible by adopting the culture in a formal education environment. This effort is expected to help schools to get a certain position in the community. Therefore, this study attempts to promote a conceptual model of cultural branding in schools and to reveal the reasons why the model becomes an effective marketing strategy in this era.Â KeywordsBranding, School culture, Positioning, Community bond